Bladder cancer and urinary Schistosomiasis in Angola - Botelho, M.C. (2015)
Schistosomiasis haematobia is among the most prevalent parasitosis in Angola. The pathology is characterized by serious and irreversible lesions in the urogenital tract induced by chronic infection with the parasite that can eventually lead to squamous cell carcinoma of the bladder. Considering the frequency and severe morbidity observed, even in younger ages, the purpose of this study was to assess the prevalence and morbidity of S. haematobium infection in Angola. A baseline survey was conducted between November 2007 and February 2008. A randomly sample of 300 inhabitants aged 15 to 75 years old participated in this study. Prevalence of S. haematobium infection was 71.7 % (215/300). Infection was higher in females (56.3 %) but no significant difference was found in prevalence and intensity between gender and age groups. The predominant selfreported symptoms were dysuria (91.2 %), hypogastralgia (88.7 %) and haematuria (87.1%) and these symptoms were strongly associated with S. haematobium infection (p<0.05). Ultrasound and cystoscopy examinations performed in a sub-sample of 29 individuals revealed pathological conditions at the urinary tract in all examined. Considering the high prevalence of S. haematobium infections in Angola and schistosomiasis-associated bladder cancer, our results indicate that this population should be targeted for follow up and implementation of measures for treatment and control of schistosomiasis.